Activities of functional enzymes involved in C, N, and P conversion and their stoichiometry during agricultural waste composting with biochar and biogas residue amendments. (February 2022) - Wang, Nanyi; Ren, Liheng; Zhang, Jiachao; Kumar Awasthi, Mukesh; Yan, Binghua; Zhang, Lihua; Wan, Fachun; Luo, Lin; Huang, Hongli; Zhao, Keqi
Graphical abstract: Highlights: Physicochemical properties were significantly changed by biochar and biogas residue. Biochar, biogas residue addition increased activities of enzymes involved in C, N, P. Stoichiometry of C:N:P acquisition ratios were close to 1:1.5:1.5. Biogas residue significantly decreased the potential C:P and N:P acquisition ratios. WSC and moisture were the crucial factors influencing enzyme activities. Abstract: This experiment was carried out to explore the effects of biochar, biogas residue and their combination amendment on enzyme activities and their stoichiometry during agricultural waste composting. A comprehensive analysis of the variation in, and stoichiometric correlations between, β-glucosidase (BG), N-acetylglucosaminidase (NAG), leucine aminopeptidase (LAP), and alkaline phosphatase (AKP) were determined. The results showed that biochar, biogas residue, and their combined addition significantly increased those enzyme activities. The potential C:P and N:P acquisition activities represented by ln(BG): ln(AKP) and ln(LAP + NAG): ln(AKP), were significantly decreased with biogas residue addition. BG, NAG and LAP were significantly negatively correlated with temperature, organic matter and water-soluble carbon. Redundancy analysis also showed that moisture and water-soluble carbon were significantly related to the variations of enzyme activities. Biochar and biogas residue changed the characteristics of the composting substrate, thus affecting the activity and stoichiometry of functional enzymes involved in C, N and P cycling.